Reanimating the English historical novel in the twenty-first century – the case of David Mitchell’s "The Thousand Autumns of Jacob de Zoet" - Kucała, Bożena (Adam Mickiewicz University, 2018)
This article argues that David Mitchell’s novel "The Thousand Autumns of Jacob de Zoet" (2010) represents a new variation of the genre of historical fiction. The historical novel in Britain has risen to prominence since the 1980s and in the twenty-first century this strong interest in the past continues. Placing David Mitchell’s book in the context of recent historical fiction, the article takes account of Joseph Brooker’s hypothesis that, together with Hilary Mantel’s Tudor novels, "The Thousand Autumns of Jacob de Zoet" may be indicative of an emergent trend in the contemporary English historical novel. The purpose of the article is to identify and explore Mitchell’s key strategies of writing about history. It is argued that, departing from the prevalent mode of historiographic metafiction, Mitchell’s book adheres to some of the traditional tenets of the genre while achieving the Scottian aim of animating the past in innovative ways. The analysis leads to the conclusion that the use of the present tense, the subjective perspectives, and the exclusion of foreknowledge lend the novel dramatic qualities.
Keywords: David Mitchell; historical novel; twenty-first century English literature; time in narrative; genre